CARE BEYOND CURE: CANCER CARE CENTER IN KOTA BARU PARAHYANGAN WITH A HEALING ENVIRONMENT APPROACH - Andari Saffanah, Qinthara
Cancer is a highly deadly non-communicable disease, and the number of cases continues to rise each year. In 2020, Indonesia reported nearly 397,000 cancer cases with over 234,000 cancer-related deaths, making cancer the third leading cause of death in the country. In cancer treatment, there are two main goals: curative and palliative. Curative treatment aims to cure cancer, while palliative care aims to improve the quality of life for cancer patients. Palliative care involves addressing the physical, psychological, emotional, and social aspects of patients. However, in Indonesia, palliative care is often misunderstood as a last resort. A shift in mindset is needed to integrate palliative care early on and not just as a final alternative. The use of a healing environment approach is introduced as an effort to improve the quality of life for cancer patients by enhancing the physical and psychological aspects of the care environment. This concept emphasizes that a positive environment can aid the healing process. The environment has a significant impact on patient well-being, and palliative care should encompass these factors. Through this approach, cancer care facilities can create a much-needed healing atmosphere for patients. By building healthcare facilities that combine palliative cancer care with the healing environment and supportive design concept, the goal is to improve the quality of life for cancer patients by providing medical care and physical, psychological, social, and spiritual support for patients, families, and caregivers. Additionally, these facilities emphasize the importance of education and training for the workforce and volunteers involved in palliative care.